Using Diffuse Reflectance Spectroscopy to Distinguish Tumor Tissue From Fibrosis in Rectal Cancer Patients as a Guide to Surgery. Issue 7 (3rd December 2019) - Baltussen, Elisabeth J.M.; Brouwer de Koning, Susan G.; Sanders, Joyce; Aalbers, Arend G.J.; Kok, Niels F.M.; Beets, Geerard L.; Hendriks, Benno H.W.; Sterenborg, Henricus J.C.M.; Kuhlmann, Koert F.D.; Ruers, Theo J.M.
Abstract : Background and Objectives: In patients with rectal cancer who received neoadjuvant (chemo)radiotherapy, fibrosis is induced in and around the tumor area. As tumors and fibrosis have similar visual and tactile feedback, they are hard to distinguish during surgery. To prevent positive resection margins during surgery and spare healthy tissue, it would be of great benefit to have a real‐time tissue classification technology that can be used in vivo. Study Design/Materials and Methods: In this study diffuse reflectance spectroscopy (DRS) was evaluated for real‐time tissue classification of tumor and fibrosis. DRS spectra of fibrosis and tumor were obtained on excised rectal specimens. After normalization using the area under the curve, a support vector machine was trained using a 10‐fold cross‐validation. Results: Using spectra of pure tumor tissue and pure fibrosis tissue, we obtained a mean accuracy of 0.88. This decreased to a mean accuracy of 0.61 when tumor measurements were used in which a layer of healthy tissue, mainly fibrosis, was present between the tumor and the measurement surface. Conclusion: It is possible to distinguish pure fibrosis from pure tumor. However, when the measurements on tumor also involve fibrotic tissue, the classification accuracy decreases. Lasers Surg. Med. © 2019 Wiley Periodicals, Inc.